Participation in Illegitimate Activities: A Theoretical and Empirical Investigation - Ehrlich, Isaac (Journal of Political Economy, 1973)
A theory of participation in illegitimate activities is developed and tested against data on variations in index crimes across states in the United States. Theorems and behavioral implications are derived using the state preference approach to behavior under uncertainty. The investigation deals directly with the interaction between offense and defense: crime and collective law enforcement. It indicates the existence of a deterrent effect of law-enforcement activity on all crimes and a strong positive correlation between income inequality and crimes against property. The empirical results also provide some tentative estimates of the effectiveness of law enforcement in reducing crime and the resulting social losses.